Caracteriza??o morfoagron?mica e estudo da heran?a gen?tica paraa cor do fruto em Physalis ixocarpa Brot. - Pereira, Janyne dos Santos (2025)
The Physalis genus, belonging to the Solanaceae family, includes edible plant species. Species within this genus are known for their numerous medicinal and nutritional properties, in addition to exhibiting genetic variability. Among the plants with such potential, Physalis ixocarpa, popularly known as "cascara tomato" or "tomatillo," stands out. It originates from Mexico and is widely used in local cuisine and medicine to treat various diseases. The species exhibits genetic variability in the color of its fruits, which are differentiated into green and purple fruits, defined as the green and purple varieties. In this context, studies in genetic improvement, cultivation, and germplasm characterization have been of great importance in academia, seeking to contribute to the inclusion of new species. In Chapter 1, 10 half-sib progenies of P. ixocarpa, belonging to the UEFS Forestry Nursery, were selected?five progenies with green fruits and five progenies with purple fruits?for their morphoagronomic characterization and directed breeding. These progenies were characterized and identified based on quantitative and qualitative descriptors, and the genetic diversity of the species was confirmed. The treatments of the purple variety (R11, R21, R31, R41, and R51) showed better plant development under the proposed growing conditions. In Chapter 2, the previously obtained progenies were used for crossbreeding and subsequently obtained a backcross population. The genetic inheritance of the backcross population was studied to determine the type of inheritance, the number of genes, and the interactions involved in the expression of this trait. The fruits obtained in the F1 and backcross generations presented a standard purple coloration with varying intensities. The observed frequencies showed a deviation from the 3:1 segregation pattern, and it was possible to infer that the inheritance of fruit color follows a quantitative inheritance pattern, influenced by a pair of complementary genes with a cumulative effect.